‘I am an architect’, gender and professional identity in architecture - MacManus, Dervla; O’Donnell, Katherine (Frontiers in Sustainable Cities, 2024)
For women architects the confluence of gender and professional identity has remained unresolved since their admittance to the profession of architecture. The past decade has seen a resurgence in the use of the term 'women in architecture' coupled with renewed debate around its use as well as challenges from feminist historians and theorists to recognise other forms of architectural practices and identities.The research presented here examines the interplay between gender and professional identity of those working within, and outside of, architectural professional practice in Ireland. Combining questions on gender and professional identity from a large survey (n=684) and 23 semi-structured interviews, in this article we suggest that the relationship between gender and professional identity for architects, especially women architects, is multifaceted and at times contradictory and paradoxical.Launched in March 2023, the Irish Architecture Career Tracker Survey received over 680 completed online questionnaires. The respondents, ranging in age from 20 to 72, were asked 'How important is being a woman/man to the way you think about your career?'. Perhaps unsurprisingly, the results for men and women are almost the inverse of one another. Male respondents tended towards 'being a man is not at all important to the way I think about my career', at 45%, while female respondents tended towards the opposite 'being a woman is extremely important to the way I think about my career' at 41%. Another key question asked was whether or not 'The term 'woman in architecture' is an important reflection of who I am professionally'? Just 40% of female participants agreed with this statement. In the 23 semi-structured interviews which followed the survey these two topics were explored providing rich qualitative. Interviewees were both male and female and ranged in age from 32 to 62. When analysed using a Reflexive Thematic Approach, I identified six themes which, when taken together, show a difficult and at times contradictory and paradoxical confluence of gender and professional identity, especially, but not only for female architects.